Fluxes of CH4 and CO2 from soil and termite mounds in south Sudanian savanna of Burkina Faso (West Africa) - Brümmer, Christian; Papen, Hans; Wassmann, Reiner; Brüggemann, Nicolas (Global biogeochemical cycles, 2009)
The contribution of West African savanna ecosystems to global greenhouse gas budgets is highly uncertain. In this study we quantified soil‐atmosphere CH4 and CO2 fluxes in the southwest of Burkina Faso from June to September 2005 and from April to September 2006 at four different agricultural fields planted with sorghum (n = 2), cotton, and peanut and at a natural savanna site with termite (Cubitermes fungifaber) mounds. During the rainy season both CH4 uptake and CH4 emission were observed in the savanna, which was on average a CH4 source of 2.79 and 2.28 kg CH4‐C ha−1 a−1 in 2005 and 2006, respectively. The crop sites were an average CH4 sink of −0.67 and −0.70 kg CH4‐C ha−1 a−1 in the 2 years, without significant seasonal variation. Mean annual soil respiration ranged between 3.86 and 5.82 t CO2‐C ha−1 a−1 in the savanna and between 2.50 and 4.51 t CO2‐C ha−1 a−1 at the crop sites. CH4 emission from termite mounds was 2 orders of magnitude higher than soil CH4 emissions, whereas termite CO2 emissions were of the same order of magnitude as soil CO2 emissions. Termite CH4 and CO2 release in the savanna contributed 8.8% and 0.4% to the total soil CH4 and CO2 emissions, respectively. At the crop sites, where termite mounds had been almost completely removed because of land use change, termite fluxes were insignificant. Mound density‐based upscaling of termite CH4 fluxes resulted in a global termite CH4 source of 0.9 Tg a−1, which corresponds to 0.15% of the total global CH4 budget of 582 Tg a−1, hence significantly lower than those obtained previously by biomass‐based calculations. This study emphasizes that land use change, which is of high relevance in this region, has particularly affected soil CH4 fluxes in the past and might still do so in the future.